DT-MSOF Strategy and its Application to Reduce the Number of Operations in AHP - Fazmah Arif Yulianto; Kuspriyanto Kuspriyanto; Teguh Nurhadi Suharsono (LPPM ITB, 2018)
A computing strategy called Double Track